Technical efficiency of wheat growing farmers of Nepal - Adhikari, Surya Prasad; Ghimire, Yuga Nath; Timsina, Krishna Prasad; Subedi, Sanjiv; Kharel, Meena (Journal of Agriculture and Natural Resources, 2021)
Wheat is a major staple food crop of Nepal, so it is necessary to increase its productivity. However, the national average wheat productivity of Nepal is low as compared to other neighboring countries. This study employed a Cobb-Douglas stochastic production frontier model to examine the technical efficiency and its determinants using randomly selected household data from 343 wheat farmers from four districts of Nepal. Maximum likelihood estimation results showed that wheat production responded positively to an increase in the quantity of inorganic fertilizer, whereas it was detrimental to seed rate. Likewise, the study found that farmers were not technically efficient with a mean technical efficiency of 81%. The result showed irrigation, herbicides, sowing time, Farm Yard Manure (FYM), and wheat varieties were statistically significant factors that affect the technical efficiency of wheat farmers. Furthermore, to increase wheat productivity, farmers should use better irrigation, appropriate weed management practices, optimum sowing time, and adoption of recent improved varieties. Findings suggest that the technical efficiency of wheat farmers could be enhanced by practicing optimum use of inputs and improving the inefficiency factors